Teaching Physics Through Jigsaw Technique of Cooperative Learning - Muhammad Khan; Farkhanda Rasheed Choudhry Choudhry (Iranian Journal of Educational Research)
Objective: Female students consider physics a difficult subject and like physics less than chemistry and biology. Cooperative learning is considered as an effective student-centered teaching methodology. The jigsaw technique of cooperative learning is successfully used to improve students' academic achievement, knowledge retention, and students’ attitudes. The present study was conducted to compare the effectiveness of the jigsaw technique of cooperative learning with the traditional lecture-based teaching method for pre-medical female students. Methods: It was an experimental study in which Pretest-Posttest true experimental design was used.  Fifty-six female pre-medical students of Federal Government Degree College for Women Bannu were divided into control and experimental groups.  The experimental group was taught with the jigsaw technique of cooperative learning whereas the control group was taught with the traditional lecture method. Research tools to assess students' academic performance, retention of the knowledge, and attitude toward learning physics were developed and validated. Results: After three months of treatment, the performance of both groups was analyzed using an independent sample t-test.  A statistically significant difference was noted between the post-test scores of the two groups. Conclusions: The jigsaw learning technique was found to be an effective technique and recommended as a proper method for teaching physics.